Des prisons médiatiques et des prisonniers. L'institution carcérale et la pénalité face aux évolutions de l'espace public - Gwenola Ricordeau (Pontifícia Universidade Católica do Rio Grande do Sul, 2009)
The article focuses on relations between the public space, the convicts and the prison institution, within the private/public boundaries are continually negotiated. The prison's qualification as a "total institution" is increasingly discussed, since its growing opening to the outside can be observed and democratization process allow prisoners¿ access to global information and even their freedom of expression. But inmates, as their relatives, are dismissed from the recurring debate about the required prison reform. Detention conditions' normalization makes sentences looking like games (the "reality-tv" ones) and it is increasingly difficult to distinguish inside from outside, because of the latter is invaded by video surveillance and virtual phenomenons. Penalty evolutions resulte in revolution of and in convicts' private space.